The impact of novel exercise criteria and indices for the diagnostic and prognostic ability of exercise testing. - Michaelides, A; Tousoulis, D; Raftopoulos, L; Antoniades, C; Tsiachris, D; Stefanadis, C (2010)
Exercise testing (ET) stands as one of the most easy, affordable, cost effective, non invasive methods for diagnosing coronary heart disease. Its sensitivity, specificity and prognostic value, especially in the prime era of its implementation in the cardiac diagnostic procedure, is relatively limited. Novel exercise criteria and indices based either on ST segment changes or ST segment independent parameters, such as "Athens QRS score", have greatly improved the diagnostic ability and accuracy of ET. Complex ECG-derived indices linked to ST changes along with the use of right-sided precordial leads have also enhanced the diagnostic accuracy of ET with respect to the extent of ischemic heart disease and the detection of specific culprit vessels. ET contains also a prognostic value, since several ET-derived parameters have been associated with adverse outcome, including ST changes, blood pressure and heart rate response to exercise and duration of exercise.